Relationship Between Narcissistic Tendencies and Social Media Addiction in Instagram Using Student University: Hubungan Antara Kecenderungan Narsistik dengan Adiksi Media Sosial pada Mahasiswa Pengguna Instagram Universitas - Wenny Widiyanti; Widyastuti (Academia Open, 2022)
This quantitative research study investigates the presence of narcissistic tendencies and their association with social media addiction in students using Instagram at Muhammadiyah University of Sidoarjo. With a sample size of 300 students selected through quota sampling technique, the study employed the Berge Social Media Addiction Scale (BSMAS) and Narcissistic Personality Inventory (NPI) scale for data collection. Utilizing Pearson's product-moment correlation analysis in SPSS, the findings reveal a significant positive relationship between narcissistic tendencies and social media addiction (rxy = 0.125, p = 0.031 < 0.05). The study's implications suggest that approximately 2.3% of social media addiction can be attributed to narcissistic tendencies among university students. These results contribute to a deeper understanding of the interplay between personality traits and online behavior, urging further research and interventions to address the impact of narcissism on social media engagement. Highlights: The study explores the relationship between narcissistic tendencies and social media addiction among university students on Instagram. The research utilizes quantitative methods and correlational analysis to examine the association between narcissistic tendencies and social media addiction. Findings reveal a significant positive relationship between narcissistic tendencies and social media addiction among students, highlighting the influence of personality traits on online behavior. Keywords: narcissistic tendency, social media addiction, university students, Instagram, correlation